Pembelajaran Kolaboratif Berbantuan Teknologi dalam Matematika: Tantangan dan Peluang (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
This research employs a Systematic Literature Review approach, aimed at exploring technology-enhanced collaborative learning in mathematics education, with a focus on the challenges and opportunities presented. Indexed sources such as Scopus, the Directory of Open Access Journals (DOAJ), and Google Scholar published between 2015 and 2024 were analyzed. The findings indicate that technology not only functions as an aid but also transforms the way students interact and learn. Digital platforms provide opportunities for students to express ideas, give feedback, and engage in reflection, which are crucial in the collaborative learning process. Active student engagement contributes to the enhancement of conceptual understanding and the development of critical and creative thinking skills necessary in an ever-changing world. Collaborative learning models that leverage technology have proven effective in improving students' mathematics learning outcomes, particularly among high school students. Although challenges such as teachers' readiness to use technology and device accessibility exist, the opportunities presented are significantly greater. With the right approach, mathematics education can harness technology to deliver more innovative and engaging teaching methods. This research concludes that the utilization of technology can assist students in understanding abstract mathematical concepts and overcoming learning difficulties